2018
DOI: 10.1155/2018/8764801
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of Neighborhood Residents’ Cognition of and Participation in Low-Carbon Behaviors in Wuhan, China

Abstract: This paper analyzed neighborhood residents’ cognition of and participation in low-carbon behaviors, basing on a questionnaire survey launched in a neighborhood in Wuhan, China. Results indicate that most respondents concerned the low-carbon impact on their daily lives and expected the government to make differences in low-carbon transition. Neighborhood residents’ participation in low-carbon behaviors was mainly reflected in three aspects: home energy conservation (HEC), efficient resource consumption (ERC), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Peng et al analyzed neighborhood residents' cognition of and participation in low-carbon behaviors. The results showed that neighborhood residents get involved in low-carbon behaviors through home energy conservation (HEC), efficient resource consumption (ERC), and recycling habits (RH) [64].…”
Section: Research Trends Development and Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peng et al analyzed neighborhood residents' cognition of and participation in low-carbon behaviors. The results showed that neighborhood residents get involved in low-carbon behaviors through home energy conservation (HEC), efficient resource consumption (ERC), and recycling habits (RH) [64].…”
Section: Research Trends Development and Hotspotsmentioning
confidence: 99%
“…Many studies have focused on the low-carbon transition and public awareness/behavior [62][63][64][65][66][67][68][69][70] However, this research topic lacks a comprehensive and systematic review. Therefore, this study analyzed the trends, progress, status, and hotspots of studies on low-carbon transition and public awareness/behavior through literature from the Web of Science (WoS) database, including countries/regions contribution analysis, institution contribution analysis, keyword analysis, and journal analysis.…”
Section: Introductionmentioning
confidence: 99%